Respuesta :
We are given:
2x + 5 - 3x = 8(x + 1)
We can start with several things. First, we can combine the x terms on the left side of the equation, and apply the distributive property on the right side of the equation.
5 - x = 8x + 8
Now, we can add x to both sides, and subtract 8 from both sides to isolate the variable.
5 - x = 8x + 8
-8 + x + x -8
We end up with:
9x = -3
By dividing both sides by 9, we get x = [tex]-\frac{1}{3}[/tex].
If you want to check your answer, just plug x in!
2([tex]-\frac{1}{3}[/tex]) + 5 - 3([tex]-\frac{1}{3}[/tex]) = 8([tex]-\frac{1}{3}[/tex] + 1)
[tex]-\frac{2}{3}[/tex] + 5 + 1 = [tex]-\frac{8}{3}[/tex] + 8
[tex]-\frac{2}{3}[/tex] + [tex]\frac{18}{3}[/tex] = [tex]-\frac{8}{3}[/tex] + [tex]\frac{24}{3}[/tex]
[tex]\frac{16}{3}[/tex] = [tex]\frac{16}{3}[/tex]
As you can see, [tex]\frac{16}{3}[/tex] = [tex]\frac{16}{3}[/tex] as a result of having x = [tex]-\frac{1}{3}[/tex].
First you must distribute the 8 to the numbers inside the parentheses
2x + 5 - 3x = 8 (x + 1)
2x + 5 - 3x = 8*x + 1*8
2x + 5 - 3x = 8x + 8
Now you must combine like terms (let's first start with the like terms on the left side). This means the numbers with the same variables must be combined...
-3x + 2x = -x
so...
-x + 5 = 8x + 8
Now you must combine like terms by combining -x with 8x. To do this first add 1x to both sides (what you do on one side you must do to the other). Since x is negative on the left side, addition (the opposite of subtraction/negative) will cancel it out (make it zero) from the left side and bring it over to the right side.
-x + x + 5 = 8x + x + 8
0 + 5 = 9x + 8
5 = 9x + 8
Now bring 8 to the left side by subtracting 8 to both sides (what you do on one side you must do to the other). Since 8 is being added on the right side, subtraction (the opposite of addition) will cancel it out (make it zero) from the right side and bring it over to the left side.
5 - 8 = 9x + 8 - 8
-3 = 9x
Next divide 9 to both sides to finish isolating x. Since 9 is being multiplied by x, division (the opposite of multiplication) will cancel 9 out (in this case it will make 9 one) from the right side and bring it over to the left side.
-3/9 = 9x/9
x = [tex]\frac{-1}{3}[/tex]
Hope this helped!
~Just a girl in love with Shawn Mendes